New insights into Oculina patagonica coral diseases and their associated Vibrio spp. communities - Rubio-Portillo, Esther (Nature Publishing Group, 2014)
Bleaching of Oculina patagonica has been extensively studied in the Eastern Mediterranean Sea, although no studies have been carried out in the Western basin. In 1996 Vibrio mediterranei was reported as the causative agent of bleaching in O. patagonica but it has not been related to bleached or healthy corals since 2003, suggesting that it was no longer involved in bleaching of O. patagonica. In an attempt to clarify the relationship between Vibrio spp., seawater temperature and coral diseases, as well as to investigate the putative differences between Eastern and Western Mediterranean basins, we have analysed the seasonal patterns of the culturable Vibrio spp. assemblages associated with healthy and diseased O. patagonica colonies. Two sampling points located in the Spanish Mediterranean coast were chosen for this study: Alicante Harbour and the Marine Reserve of Tabarca. A complex and dynamic assemblage of Vibrio spp. was present in O. patagonica along the whole year and under different environmental conditions and coral health status. While some Vibrio spp. were detected all year around in corals, the known pathogens V. mediteranei and V. coralliilyticus were only present in diseased specimens. The pathogenic potential of these bacteria was studied by experimental infection under laboratory conditions. Both vibrios caused diseased signs from 24 °C, being higher and faster at 28 °C. Unexpectedly, the co-inoculation of these two Vibrio species seemed to have a synergistic pathogenic effect over O. patagonica, as disease signs were readily observed at temperatures at which bleaching is not normally observed.